Spatial variation of sediment mineralization supports differential CO2 emissions from a tropical hydroelectric reservoir - Cardoso, Simone J.; Vidal, Luciana O.; Mendonça, Raquel F.; Tranvik, Lars J.; Sobek, Sebastian; Roland, Fabio (Frontiers in Microbiology, 2013)
Substantial amounts of organic matter (OM) from terrestrial ecosystems are buried as sediments in inland waters. It is still unclear to what extent this OM constitutes a sink of carbon, and how much of it is returned to the atmosphere upon mineralization to carbon dioxide (CO2). The construction of reservoirs affects the carbon cycle by increasing OM sedimentation at the regional scale. In this study we determine the OM mineralization in the sediment of three zones (river, transition and dam) of a tropical hydroelectric reservoir in Brazil as well as identify the composition of the carbon pool available for mineralization. We measured sediment OC mineralization rates and related them to the composition of the OM, bacterial abundance and pCO2 of the surface water of the reservoir. Terrestrial OM was an important substrate for the mineralization. In the river and transition zones most of the OM was allochthonous (56 % and 48 %, respectively) while the dam zone had the lowest allochthonous contribution (7 %). The highest mineralization rates were found in the transition zone (154.80 ± 33.50 mg C m-2 d-1) and the lowest in the dam (51.60 ± 26.80 mg C m-2 d-1). Moreover, mineralization rates were significantly related to bacterial abundance (r2 = 0.50, p < 0.001) and pCO2 in the surface water of the reservoir (r2 = 0.73, p < 0.001). The results indicate that allochthonous OM has different contributions to sediment mineralization in the three zones of the reservoir. Further, the sediment mineralization, mediated by heterotrophic bacteria metabolism, significantly contributes to CO2 supersaturation in the water column, resulting in higher pCO2 in the river and transition zones in comparison with the dam zone, affecting greenhouse gas emission estimations from hydroelectric reservoirs.